Saline Flush versus Chest x ray in Confirmation of Central Venous Catheter Placement; a Diagnostic Accuracy Study - Esmailian, Mehrdad; Azizkhani, Reza; Najafi, Nazila (Archives of Academic Emergency Medicine, 2017)
Introduction: Central venous catheterization (CVC) is a commonly performed procedure in critically ill patients of emergency department. This study was designed to compare the diagnostic accuracy of saline flush with CXR in confirmation of above-the-diaphragm CVC placement. Methods: This prospective cross sectional study was conducted on adult patients in need of CVC placement in emergency department. Placement Confirmation was performed with saline flush method and CXR, then chest computed tomography (CT) was performed as the gold standard. The screening performance characteristics of the two methods were calculated and compared using SPSS 21 and STATA 11. Results: 103 cases with the mean age of 57.18±9.3 (35 -80) years were studied (52.4% male). The mean duration of procedure was 2.5±1.24 in saline flush and 32.11±5.52 minutes in CXR method (P<0.001(. The area under the ROC curves for saline flush and CXR in confirmation of CVC placement were 0.90 (95%CI: 0.70 – 0.100) and 0.80 (95%CI: 0.55 – 0.100), respectively (p = 0.317). The sensitivity, specificity, positive and negative predictive value, and positive and negative likelihood ratio of saline flush were 80%, 100%, 100, 98.9%, Infinity, and 0.01, respectively. These measures were 60%, 100%, 100%, 98%, Infinity, and 0.02 for CXR, respectively. Conclusion: It seems that saline flush method could be considered as a safe, rapid, and accurate bedside method for CVC placement confirmation in emergency department.